Stereoselective reductive alkylation of 2,5-disubstituted pyrroles: a role for naphthalene in the partial reduction of heterocycles - Donohoe, T; Harji, R; Cousins, R (2000)
Lithium in ammonia promotes the stereoselective reduction of 2,5- disubstituted pyrroles: such reactions proceed with good levels of stereoselectivity, producing the trans-isomer. The stereochemistry of one of the reduced compounds was proven by X-ray crystallography. A mechanism is proposed which explains the stereoselectivity and a modification made to the reducing system that includes catalytic naphthalene and obviates the need for liquid ammonia. (C) 2000 Elsevier Science Ltd.